Reliability and Availability of FSO for different Weather Conditions (International Journal of Engineering and Computer Science, 2015)
Today Free-Space Optical communication (FSO)has overcome the radio frequency communication. This paper gives an overview of the availability of an FSO system and its different weather conditions. It describes problems that the designer faces while implementing an FSO system and to overcome that problems .Performance analysis of a system for different weather conditions is carried out. Calculation of attenuation due to fog by using KIM and KRUZE Model and other parameters such as received power, BER and Q factor are analyzed. FSO provides data rate upto 1 gbps . A laser diode at the transmittter side of 850nm and the PIN diode as a photodetector at the receiver side is used. It is possible to calculate visibility from the measured data which is the main factor for estimation the availability and reliability of FSO link . The system link is established using simulation software optisystem and system characteristics is studied.